1989
DOI: 10.1007/bf01311362
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of rat parvovirus in athymic rats

Abstract: Euthymic (SD or outbred rnu/+) and athymic (rnu/rnu) rats were inoculated oronasally or intraperitoneally with the RV-Y strain of rat virus when they were 2 days or 4 weeks old. Clinical signs of infection in athymic infants were similar to those in euthymic infants, but significantly more athymic infants died. Some infants developed anemia and thrombocytopenia. After inoculation of infants. RV-Y was detected in surviving euthymic rats for 7 weeks and in surviving athymic rats for at least 10 weeks. After oron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…We subsequently found that some rats inoculated with RV by the oronasal route at 2 days of age harbored infection for at least 6 months and excreted virus for up to 11 weeks, well after the onset of antiviral immunity (32). Susceptibility to persistent infection appeared to be age dependent, since randomly bred rats inoculated as young adults with the Yale strain of RV (RV-Y) rarely remained infected for more than 4 weeks unless they were immunodeficient (25,32).…”
Section: The Results Demonstrate That Vasculotropism Is a Significantmentioning
confidence: 99%
See 2 more Smart Citations
“…We subsequently found that some rats inoculated with RV by the oronasal route at 2 days of age harbored infection for at least 6 months and excreted virus for up to 11 weeks, well after the onset of antiviral immunity (32). Susceptibility to persistent infection appeared to be age dependent, since randomly bred rats inoculated as young adults with the Yale strain of RV (RV-Y) rarely remained infected for more than 4 weeks unless they were immunodeficient (25,32).…”
Section: The Results Demonstrate That Vasculotropism Is a Significantmentioning
confidence: 99%
“…Preliminary studies of athymic rats demonstrated that T-cell-mediated immunity is essential to eliminate infection (25) and that humoral immunity alone suppresses but does not eliminate preexisting infection (23). These and other results (32) also indicated that mature tissues contain cells susceptible to infection, but they did not confirm the distribution or replication status of virus during persistent infection or explore further the role of host immunity.…”
Section: The Results Demonstrate That Vasculotropism Is a Significantmentioning
confidence: 99%
See 1 more Smart Citation
“…Infections may result in clinical disease and pathological changes, especially in perinatal and immunodeficient animals [3,12,18,32,33,35,37]. Furthermore, some microor-ganisms indigenous to laboratory animal species are zoonotic agents that have caused disease in humans [1,8,17,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…To investigate further the role of passive immunity in modulating RV infection, athymic and euthymic rats were challenged with RV before, during or after passive immunization. Athymic rats were included because they are more susceptible to RV-induced disease and persistent infection and do not develop humoral immunity to RV [3].…”
Section: Introductionmentioning
confidence: 99%